SPATIAL STRUCTURE OF SOME BUSINESS ACTIVITIES IN THE AREA OF SMALL AND MID-SIZE CITIES (PERI-URBAN AREA) IN THE COUNTY OF ZAGREB - Jelena LONČAR (Analele Universităţii din Oradea: Seria Geografie, 2017)
In this paper the purpose of the research was to register, map and analyse business entities in the small and mid-size cities in the County of Zagreb, and on this basis get conclusions of the economic and spatial structure in the area. The analysed area includes the central parts of eight cities, i.e. the areas with the highest number of business activities. Since the most of the activities are concentrated in the cities, municipalities in the County are not included into this research. Census of business activities shows certain patterns i.e. that most of the cities in analysed area are still getting behind in number and quality of business entities according to those in the City of Zagreb and that polarization of business structure is obvious between those two areas.